Pediatric Oncologic Imaging: A Key Application of Combined PET/MRI - Gatidis, S.; la Fougère, C.; Schaefer, J. F. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Pediatric imaging has been identified as a key application of combined whole-body PET/MRI. First studies have revealed the clinical feasibility and possible advantages of PET/MRI over PET/CT and MRI. Besides a significant reduction in radiation exposure of about 50 – 75 %, combined whole-body PET/MRI offers the diagnostic advantage of the multiparametric characterization of pathophysiologic processes and helps reduce the number of necessary imaging studies. However, very few studies focusing on pediatric PET/MRI have been published to date. Additional studies are necessary in order to fully appreciate the clinical impact of this novel method. This review article shall summarize the existing literature concerning pediatric PET/MRI and give insight into the practical experience derived from over 160 pediatric PET/MRI examinations that were performed in Tübingen.Key Points:• Combined PET/MR is a promising imaging modality in pediatric oncology.• Using combined PET/MRI, diagnostic radiation exposure of pediatric patients and the number of necessary imaging studies can be reduced.• Further clinical studies are necessary in order to define specific indications for combined PET/MRI in pediatric radiology.Citation Format:• Gatidis S, la Fougère C, Schaefer J F Pediatric Oncologic Imaging: A Key Application of Combined PET/MRI. Fortschr Röntgenstr 2016; 188: 359 – 364
Keywords: PET/MR; children; oncology; FDG